spatial modeling of summer precipitation in North-west of Iran - hossein asakereh; robab razmi (تحقیقات کاربردی علوم جغرافیایی)
In the present study, the main aim was the spatial evaluation summer rainfall of northwest of Iran based on30 stations in northwest of Iran during 30 years of statistical period (1985-2014). An attempt, using geo-statistical modeling by ordinary least squares (OLS) and geographically weighted regression (GWR) procedures, was also made. The results represented that the GWR model with higher S2, lower residuals and lower RMSE is an optimized geo-statistical model for rainfall modeling of this area. This model can explain spatio-temporal rainfall distribution in northwest of Iran in a diversified topographical and geographical background. This model revealed that two spatial factors including elevation and slope, have the most important role in the summer rainfall behavior.Therefore Elevations in the mountainous and eastern parts of Lake Urmia, Latitude in the northern regions and slopes in the east of the region, have the most role in the spatial variations of summer precipitation in northwestern Iran.